2005
DOI: 10.1098/rspb.2005.3054
|View full text |Cite
|
Sign up to set email alerts
|

Socially transmitted mate preferences in a monogamous bird: a non-genetic mechanism of sexual selection

Abstract: There is increasing evidence that animals can acquire mate preferences through the use of public information, notably by observing (and copying) the mate preferences of others in the population. If females acquire preferences through social mechanisms, sexual selection could act very rapidly to spread the preference and drive elaboration of the preferred trait(s). Although there are reports of 'mate-choice copying' in polygynous species, there is no clear evidence for this process in monogamous species. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…White and Galef (2000) show that, in Japanese quails, females that have previously observed a conspecific male mating, may successively show a preference not only for that specific male, but also for males that share his characteristics. Similar results have been observed in zebra finches (Swaddle et al, 2005) and guppies (Godin et al, 2005) and also in an invertebrate, Drosophila melanogaster (Mery et al, 2009). According to this hypothesis female matechoice copying is a form of cultural transmission (Kirkpatrick and Dugatkin, 1994), because mate preferences evolve through mechanisms of social learning.…”
Section: S Castellano Et Al / Behavioural Processes XXX (2012) Xxx-xxxsupporting
confidence: 84%
“…White and Galef (2000) show that, in Japanese quails, females that have previously observed a conspecific male mating, may successively show a preference not only for that specific male, but also for males that share his characteristics. Similar results have been observed in zebra finches (Swaddle et al, 2005) and guppies (Godin et al, 2005) and also in an invertebrate, Drosophila melanogaster (Mery et al, 2009). According to this hypothesis female matechoice copying is a form of cultural transmission (Kirkpatrick and Dugatkin, 1994), because mate preferences evolve through mechanisms of social learning.…”
Section: S Castellano Et Al / Behavioural Processes XXX (2012) Xxx-xxxsupporting
confidence: 84%
“…[53,54]). Copying effects, however, can be more general, with females showing preferences for novel males that are physically similar to males observed with other females [9,12,13]. This generalization of preferences for certain traits, and not just preferences for specific individuals, is important as it allows social transmission to have more wide-reaching consequences on the evolution of certain anatomical traits and preferences [55].…”
Section: Cultural Variation In Preference and The Spread Of Preferencmentioning
confidence: 99%
“…(a) Mate-choice copying in non-human species: a brief review Mate-choice copying has been observed among females in a number of different non-human species [3][4][5][6], including fish [7][8][9][10] and bird species [11][12][13]. Such studies have generally shown that when females observe another female (the model) to be paired with one of two males (the targets), they are subsequently more likely to prefer the target male they had seen paired with the model over the male that was not paired with the model.…”
Section: Social Learning and Mate Preferences In Non-human Species Anmentioning
confidence: 99%
“…In addition to sexual imprinting early in life, using parents as role models when choosing a mate, birds may use social information gained later in life such as 'public information' and eavesdropping by observing the mating choices of other individuals [31]. Costs and benefits may differ between the sexes, and so also their use of information [32], e.g.…”
Section: Introductionmentioning
confidence: 99%